Serotonin produces long-term changes in the excitability of Aplysia sensory neurons in culture that depend on new protein synthesis - Dale, N (J Neurosci, 1987)
When isolated and grown in cell culture, the sensory and motor neurons of the gill withdrawal reflex of Aplysia readily form synaptic connections. Repeated exposures to 5-HT cause facilitation of the synaptic connections between co-cultured sensory and motor neurons lasting at least 24 hr. As a first step toward understanding the locus and the mechanisms underlying this long-term synaptic facilitation, we have examined the membrane excitability of the isolated presynaptic sensory neurons grown alone in dissociated cell culture. Four repeated applications of 1 microM 5-HT caused a significant increase in the excitability of sensory neurons, lasting at least 24 hr. This resembles the short-term changes in excitability seen in response to a single application of 5-HT. Unlike the short-term effect, this long-lasting change was blocked by exposure of the cells during the 5-HT treatment to 10 microM anisomycin, an inhibitor of protein synthesis. Thus, like the synaptic facilitation, the long-term change in excitability of the isolated presynaptic neurons differs from the short-term in requiring the synthesis of new protein. This finding suggests that the sensory neuron uses gene products to modulate membrane currents in its long- term response to repeated external stimuli that are not required in its short-term response to a single stimulus.